Penyajian laporan keuangan daerah sesuai PSAP 71 tentang standar akuntansi pemerintahan di kantor Badan Pengelolaan Keuangan Aceh - Husnawati, Husnawati; Zahara, Rina; Zulkarnain, Teuku (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This study aims to evaluate the presentation of local financial statements at the Aceh Financial Management Agency office in the context of conformity with the guidelines of Government Accounting Standards (PSAP) 71. Statement of Government Accounting Standards (PSAP 71) regulates local government financial statements, focusing on disclosures related to fixed assets. The evaluation phase includes an assessment of compliance with the standard as well as the quality of the information presented, with a focus on transparency and accountability in asset management. With the existence of PSAP 71, it is expected that financial statements can present relevant, reliable and useful information. This research methodology uses a qualitative approach with data collection techniques. This research was conducted in the time span of 2022-2023. The results showed that although the Regional financial statements in Aceh Province had been prepared with reference to PSAP 71, there were still some discrepancies in the application of accounting principles. For example, it can be in the form of fixed asset valuations that are not updated, so that the reported values do not reflect the actual conditions. Based on the analysis, this study recommends several corrective measures. First, the development of a better and integrated accounting information system to facilitate the process of collecting and presenting financial data.